2018
DOI: 10.1038/s41430-017-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3-fortified milk did not affect glycemic control, lipid profile, and anthropometric measures in patients with type 2 diabetes, a triple-blind randomized clinical trial

Abstract: Overall, daily consumption of one cup of milk containing 1000 IU vitamin D for 9 weeks substantially improved vitamin D deficiency in patients with type 2 diabetes but it did not affect cardiometabolic parameters over that of plain milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In a large-scale study, Al-Daghri et al 56 found that WHR was less significant than other anthropometric measures of obesity regarding the strength of association with VD status. However, the inverse correlation observed between VD levels with waist 49,50,57,58 or hip 51,53,59,60 circumferences in previous studies may result due to subcutaneously visceral adiposity alterations. 39,46,54,61 Similar alterations were also noted in elderly Korean women.…”
Section: Discussionmentioning
confidence: 66%
“…In a large-scale study, Al-Daghri et al 56 found that WHR was less significant than other anthropometric measures of obesity regarding the strength of association with VD status. However, the inverse correlation observed between VD levels with waist 49,50,57,58 or hip 51,53,59,60 circumferences in previous studies may result due to subcutaneously visceral adiposity alterations. 39,46,54,61 Similar alterations were also noted in elderly Korean women.…”
Section: Discussionmentioning
confidence: 66%
“…Four studies out of five used daily dose of 25 µg/d, heterogeneity was 44% in those studies. (13)(14)(15)18). The overall efficacy effect was 37.1 nmol/L (95% CI, 28.6-45.7), relating to a 1.4 nmol/L increase in 25(OH)D for each 1 µg/d ingested.…”
Section: Resultsmentioning
confidence: 95%
“…1). A total of 5 clinical trials (13)(14)(15)(16)(17) involving 59 to 101 participants ( Table 1). All studies were conducted in adult populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations